Bureaucratic Abuse In The Nigerian Civil Service: A Critical Analysis - Alabi, Tope (Advances in Social Sciences Research Journal, 2019)
As rightly observed by one of the founding fathers of Sociology, Max Weber, all modern formal organizations are bureaucratic in nature. By implication, modern complex organizations operate along bureaucratic lines. Just like other formal organization. Nigeria Federal Ministries operate bureaucracy to achieve its aims and objectives. However, there are views that tend to suggest that bureaucracy is abused by organizations by these ministries. This paper therefore takes a critical review on the extent to which bureaucratic abuses in Nigerian Federal Ministries. Existing literatures were extensively reviewed and suggestions were made based on the submissions of various scholars on bureaucratic abused in Nigeria.